2021
DOI: 10.3390/ijerph18031115
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentration of Fluoride in Patients with Alcoholic Liver Cirrhosis from the Lublin Region in Eastern Poland

Abstract: In view of previous reports, it is important to determine the relationship between liver function and the level of fluoride in the serum. The aim of this study was to investigate serum concentrations of fluoride in 72 patients with alcoholic liver cirrhosis, living in the region of Lublin (Eastern Poland) divided based on the severity of disease according to the Child-Turcotte-Pugh criteria. Higher plasma fluoride concentrations were associated with changes in liver related parameters. In all groups of analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous study showed that fluorosis could accelerate hepatic oxidative stress in animals, and the mechanism may be related to fluoride-induced hepatocyte apoptosis and autophagy ( 39 41 ). In addition, a correlation between the stage of patients with alcoholic cirrhosis and serum fluoride levels was confirmed, with elevated plasma fluoride accompanied by raised alanine aminotransferase and total bilirubin ( 42 ). In a recent population-based cross-sectional study, by monitoring fluoride concentrations in plasma and household tap water, as well as evaluating the hepatic parameters in serum, it was found that every 1 mg/mL increase in water fluoride strongly correlated with 0.93 mg/dL decreased blood urea nitrogen concentration ( 43 ).…”
Section: Discussionmentioning
confidence: 90%
“…Previous study showed that fluorosis could accelerate hepatic oxidative stress in animals, and the mechanism may be related to fluoride-induced hepatocyte apoptosis and autophagy ( 39 41 ). In addition, a correlation between the stage of patients with alcoholic cirrhosis and serum fluoride levels was confirmed, with elevated plasma fluoride accompanied by raised alanine aminotransferase and total bilirubin ( 42 ). In a recent population-based cross-sectional study, by monitoring fluoride concentrations in plasma and household tap water, as well as evaluating the hepatic parameters in serum, it was found that every 1 mg/mL increase in water fluoride strongly correlated with 0.93 mg/dL decreased blood urea nitrogen concentration ( 43 ).…”
Section: Discussionmentioning
confidence: 90%